Inelastic cross sections of relativistic protons on Lead - Zamani, M.; Stoulos, S.; Fragopoulou, M.; Manolopoulou, M.; Sosnin, N. A.; Krivopustov, M. (HNPS Advances in Nuclear Physics, 2019)
The inelastic cross section of relativistic protons in Lead was determined indirectly by measuring the neutron distribution along a Lead spallation neutron source. The spallation neutron source was irradiated by 1, 1.5 and 2 GeV protons. The experimental results were taken using passive methods. A fitting procedure has been applied to the experimental data and the results have been compared with analytical calculation of the produced hadrons’ spatial distribution based on High Energy Physics concepts. Using the beam attenuation coefficient the inelastic cross section of protons in Pb was estimated.